2017
DOI: 10.1186/s13063-016-1773-7
|View full text |Cite
|
Sign up to set email alerts
|

A home-based exercise program for children with congenital heart disease following interventional cardiac catheterization: study protocol for a randomized controlled trial

Abstract: BackgroundCardiac catheterization has opened an innovative treatment field for cardiac disease; this treatment is becoming the most popular approach for pediatric congenital heart disease (CHD) and has led to a significant growth in the number of children with cardiac catheterization. Unfortunately, based on evidence, it has been demonstrated that the majority of children with CHD are at an increased risk of “non-cardiac” problems. Effective exercise therapy could improve their functional status significantly.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…Limoee et al study showed that the implementation of a HBCR programs increases the QoL of patients after coronary artery bypass surgery ( Limoee et al, 2019 ). Also, the results of a study in the CR center of a hospital in Taiwan showed that early CR after cardiac surgery has significantly improved the physical capacity and QoL of heart transplant patients ( Du et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Limoee et al study showed that the implementation of a HBCR programs increases the QoL of patients after coronary artery bypass surgery ( Limoee et al, 2019 ). Also, the results of a study in the CR center of a hospital in Taiwan showed that early CR after cardiac surgery has significantly improved the physical capacity and QoL of heart transplant patients ( Du et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Women with CHD do not wish to be seen differently by society but can feel differences between them and women without CHD. The limitations and differences experienced in their daily lives may have caused the participants to feel that their disease controlled their lives and caused them to crave recognition [33]. Pregnancy also poses a certain health risk for women.…”
Section: Discussionmentioning
confidence: 99%
“…A Chinese version of the WeeFIM questionnaire [ 14 , 15 , 16 ] was used to estimate the functional independence of the enrolled children. The WeeFIM questionnaire was designed for primary caregivers to record their child’s abilities directly, and in 2002, Wong et al translated the questionnaire into Chinese.…”
Section: Methodsmentioning
confidence: 99%